Implementasi Kebijakan Peraturan Bersama Tahun 2014 Tentang Penanganan Pecandu Narkotika dan Korban Penyalahgunaan Narkotika Ke Dalam Lembaga Rehabilitasi di Propinsi Banten - Saobikha Nahar (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
This research discusses the handling of narcotic addicts and victims of the abuse of narcotics into the integrated rehabilitation institutions and synergies through coordination and cooperation between agencies and implementing policy in Banten Province.  The presence of Shared Rules are expected to be the solution in implementation of rehabilitation in the levels of investigation, the prosecution, the trial and the judgment synergistically and integrated. The research method used i.e. qualitative descriptive. By using the Partisipatory Action Research (PAR) approach through thematic methods. Data collection techniques are used namely observation, FGD, narrative interview and documentation. The technique used is the analysis of thematic analysis. Where as a policy implementation model used is a model developed by Merille s Grindle.